FAKTOR-FAKTOR YANG MEMPENGARUHI KEMAUAN MEMBAYAR PAJAK, WAJIB PAJAK INDIVIDU YANG MEMILIKI PEKERJAAN BEBAS (Studi pada UMKM di Semarang) - Djoko Wahjudi; Arief Himmawan (Dinamika Akuntansi Keuangan dan Perbankan, 2015)
Willingness to pay taxes is a necessary first step to carry out taxation. It's own volition arise based on many factors that influence it. This study was to find out how much influence the awareness factor to pay taxes, knowledge and understanding of tax regulations, a good perception of the effectiveness of the tax system, and the Sunset Policy jointly on the level of willingness to pay taxes in the region of UMKM Semarang. Data collection is done by collecting primary data in the form of questionnaires. The research sample consists of 131 taxpayers who have been willing to fill in questionnaires. While a decent sample processed in this study were 125 questionnaires. Method to answer the research question is processed by linear regression using SPSS. Results of research showed that: (1) consciousness of paying taxes and a significant positive effect on willingness to pay taxes. (2) Knowledge and understanding of tax regulations have a negative influence and no significant on willingness to pay taxes. (3) A good perception of the effectiveness of the tax system has positive affect and significant on willingness to pay taxes. Key words: Willingness to pay taxes, Consciousness of paying taxes, Knowledge and understanding of tax regulations, a good perception of the  effectiveness of the tax system